Enhancement of Withstand Voltage in Silicon Strain Gauges Using a Thin Alkali-Free Glass - Joon Hyub Kim; Ji-Hoon Han; Chan Won Park; Nam Ki Min (Sensors, 2020)
We present a cost-effective approach to produce silicon strain gauges that can withstand very high voltage without using any complex package design and without sacrificing any sensor performance. This is achieved by a special silicon strain gauge structure created on an alkali-free glass substrate that has a high breakdown voltage. A half-bridge silicon strain gauge is designed, fabricated, and then tested to measure its output characteristics. The device has a glass layer that is only 25–55 µm thick; it shows it is able to withstand a voltage of over 2000 V while maintaining a high degree of linearity with correlation coefficients higher than 0.9990 and an average sensitivity of 104.13. Due to their unique electrical properties, silicon strain gauges-on-glass chips hold much promise for use in advanced force and pressure sensors.